HERMENEUTIKA HUKUM ISLAM KHALEED ABOU EL FADL: Sebuah Tawaran Dalam Membendung Otoritarianisme Fatwa MUI - Muzayyin Muzayyin (Institut Agama Islam Negeri (IAIN) Manado, 2018)
Abstrak.One of the great thinkers in the contemporary era is Khaleed Abou El Fadl, a prominent public intellectual on Islamic law. Through his works, Speaking in The God’s Name: Islamic Law, Authority, and Woman, Abou El Fadl offers a frame of new methodology in the study of Islamic law by using a hermeneutics approach. Abou El-Fadl’s hermeneutics can be called the negotiated hermeneutics because the core of his hermeneutics analysis is to negotiate the role of the text (al-Qur’an, hadits, and fatwa), author (Mufti, special agent), and reader (Islamic society, common agent) in determining the meaning of authoritative text. These three parties should be a balancing and negotiating progress in which that one party ought not to dominate the determination of meaning. Abou El Fadl’s hermeneutics theory embraces the idea of autonomous and open texts. Therefore, the interpretation of the text does not always focus on efforts to locate the author’s desired intent. Hence, He further argues that integrity of text being damaged, not dynamic, and be unable to perform its functions in responding the challenges and demand of the global era due to the authoritarianism, or interpretative despotism by way of locking the will of the divine behind the text, its interpretation, or fatwa based on certain ideology as performed by those Mufti who speak in God’s name. in short, From above description emphasis the significance of Abou El Fadl’s hermeneutics in contemporary Islamic law studies is to stem the authoritarianism that has become a common phenomenon in the contemporary era. This paper using the critical-analysis of method to examines or look at critically Mufti in making various judicial decision and legal opinion (fatwa) in case of Permanent Council for Specific Research And Legal Opinion (CRLO)in Egypt and Indonesian Council of Ulama (MUI) in Indonesia that assessedreapmuchcontroversy and even rejections from part of Muslim community.Keywords:Islamic law, hermeneutics, authoritarianism, legal opinion, MUI Abstrak .Salah satu pemikir besar di era kontemporer adalah Khaleed Abou El Fadl , seorang intelektual publik terkemuka tentang hukum Islam. Melalui karyanya ,Speaking in The God’s Name: Islamic Law, Authority, and Woman, Abou El Fadl menawarkan kerangka metodologi baru dalam studi hukum Islam dengan menggunakan pendekatan hermeneutika . Hermeneutika Abou El Fadl disebut hermeneutika negosiasi karena inti dari analisis hermeneutikanya adalah menegosiasikan peran teks ( al-Qur'an , hadits , dan fatwa ), pengarang ( Mufti ,agen khusus), dan pembaca (masyarakat Islam,agen umum) dalam menentukan makna teks otoritatif .Ketiga pihak harus seimbang dan bernegosiasi di mana salah satu pihak tidak seharusnya mendominasi penentuan makna.Teori hermeneutika Abou El Fadl yang mencakup gagasan teks otonom dan terbuka sehingga penafsiran teks tidak selalu fokus pada upaya untuk mencari maksud penulis yang diinginkan . Oleh karena itu, Abou El-Fadl menyatakan bahwa integritas teks menjadi rusak, tidak dinamis , dan tidak dapat menjalankan fungsinya dalam merespon tantangan dan tuntutan era global karena otoritarianisme , atau penafsiran despotic dengan cara mengunci kehendak Tuhan di belakang teks, interpretasi, atau fatwa berdasarkan ideologi tertentu seperti yang dilakukan oleh mereka para Mufti yang mengatas namakan dirinya sebagai pembicara atas nama Tuhan. Singkatnya , dari uraian di atas pentingnya hermeneutika Abou El Fadl dalam studi hukum Islam kontemporer adalah untuk membendung otoritarianisme yang telah menjadi fenomena umum di era kontemporer. Makalah ini menggunakan metode kritis-analisis untuk menguji atau melihat secara kritis seorang Mufti dalam membuat berbagai keputusan hukum atau fatwa dalam kasus Indonesian Council of Ulama( MUI ) di Indonesia yang dinilai menuai banyak kontroversi dan bahkan beberapa penolakan dari sebagian masyarakat Muslim Kontemporer .Kata kunci :hermeneutika, hokum Islam, otoritarianisme, fatwa , MUI